Detection of Mycobacterium leprae in saliva and the evaluation of oral sensitivity in patients with leprosy - Fernanda Borowsky da Rosa; Victor Costa de Souza; Tatiana Amaral Pires de Almeida; Valdinete Alves do Nascimento; Felicien Gonçalves Vásquez; Maria da Graça Souza Cunha; Felipe Gomes Naveca (Memorias do Instituto Oswaldo Cruz, 2013)
The aim of this study was to investigate sensitivity disorders in the oral cavity related to the presence of Mycobacterium leprae in the saliva of treatment-naïve patients with leprosy in the state of Amazonas, Brazil. A cross-sectional study was conducted involving 45 subjects with leprosy. The subjects were interviewed to evaluate the sensitivity of the oral cavity. For the detection of M. leprae, saliva and slit-skin smear samples were collected. The samples were analysed using a bacteriological index (BI) protocol and the real-time quantitative polymerase chain reaction (qPCR). The results indicated that 15 of the 45 (33.3%) subjects with leprosy showed decreased oral sensitivity, which confirmed the importance of the oral cavity sensitivity evaluation. There was not a direct relationship between the presence of M. leprae in saliva and changes in oral sensitivity. Positive saliva qPCR results from six (31.6%) of 19 paucibacillary (PB) patients suggested the possibility of a new site for sample collection. Positive results using these diagnostic techniques (BI, slit-skin smear and saliva qPCR) increased to 55.5%, thus opening the possibility of combining these different techniques to increase the rate of positive diagnoses, especially in PB patients.